Pengurangan Risiko Bencana Inklusif Berbantuan Media DISABU-TUNE (Disaster Audiobook Tunanetra) bagi Siswa Tunanetra di SDLB A Negeri Banyuwangi - Benardi, Andi Irwan; Zulfa, Alfiatus; Sumarmi, Sumarmi; Sriyono, Sriyono; Yametis, Joshua Vincent Gerar; Wibowo, Novika Adi (Jurnal Pendidikan Geografi Undiksha, 2024)
The urgency of providing education about disasters for blind students is to increase the knowledge capacity of blind students about disaster mitigation, with the hope that blind students can evacuate themselves independently when a disaster occurs. Providing disaster education for blind students is important because blind people have mobility barriers, making it difficult for them to evacuate themselves when a disaster occurs. So far, inclusive disaster risk reduction efforts for students with visual impairments in Banyuwangi Regency have not been implemented properly, there are still schools that have not been completely touched by disaster education, namely SDLB A Negeri Banyuwangi. The absence of socialization efforts and the provision of disaster learning media has made students' knowledge about disasters only limited but they do not know what attitudes/steps they should take when a disaster occurs. Therefore, researchers want to contribute as an effort to increase disaster knowledge for blind students by using DISABU-TUNE media which has been adjusted to the learning characteristics of blind students. Based on the results of research that has been carried out, there is an increase in the average student learning outcomes regarding disasters from the original 51.2 to 83.4, and the test of the influence of media on students' knowledge gets the results of 0.8303, or is included in the very high category.